Development of a High-Efficient Mutation Resource with Phenotypic Variation in Hexaploid Winter Wheat and Identification of Novel Alleles in the TaAGP.L-B1 Gene - Guo, Huijun; Yan, Zhihui; Li, Xiao; Xie, Yongdun; Xiong, Hongchun; Liu, Yunchuan; Zhao, Linshu; Gu, Jiayu; Zhao, Shirong; Liu, Luxiang (Frontiers in Plant Science, 2017)
Mutated genetic resources play an important role in gene/allele characterization. Currently, there are few hexaploid winter wheat mutated resources available. Here, we developed a hexaploid winter wheat resource by inducing mutations via EMS treatment by the single seed descent method. A broad mutation spectrum with high mutation frequency (~19%) on phenotypic variations was identified. These mutations included spike, leaf and seed morphology, plant architecture and heading date variations. To evaluate the efficiency of the resource for reverse genetic analysis, allelic variations in the TaAGP.L-B1 gene, encoding the AGPase large subunit, were screened by the TILLING approach. Four missense mutations were identified and one allele in line E3-1-3, resulted in an amino acid change predicated to have severe effects on gene function. The other three mutations were predicted to have no effect. Results of gene expression patterns and grain starch content demonstrated that the novel allele in E3-1-3 altered the function of TaAGP.L-B1. Our results indicated that this mutated genetic wheat resource contained broad spectrum phenotypic and genotypic variations, that may be useful for wheat improvement, gene discovery and functional genomics.